Shaping a Sustainable Future Innovative Teaching Practices for Educating Responsible Leaders - Bustamante, Silke; Saltevo, Ellen; Schmitz, Marina; Martinovic, Martina (HWR Berlin Forschung, 2022)
This book gives insights into important factors that are shaping effective learning for sustainability and describes innovative teaching formats that will enable students to contribute to a more sustainable world in their future role as decision makers. Basic concepts in the context of sustainability-related teaching and learning are defined and the relation between learning objectives, methods, skills and outcomes is conceptualised. The book's detailed description of 23 teaching formats, including their learning objectives, course contents and structure, as well as applied methods aims at supporting lecturers and trainers in the design of their own teaching formats. With contributions by Pilar Acosta, Bimal Arora, Hasret Balcioglu, Diana Bank Weinberg, Maria Angeles Bustamante Gallego, Silke Bustamante, Julen Castillo-Apraiz, Helen Chiappini, Arrate Lasa Elguezua, Iñaki Etaio Alonso, Diego Rada Fernandez de Jauregui, Irene Garnelo-Gomez, Jonatan Miranda Gomez, Zsuzsanna Győri, Tony Henshaw, Igor Hernandez Ochoa, Mark Hoyle, Maria V. Ilieva, Divya Jyoti, Achilleas Karayiannis, Prashan S. M. Karunaratne, Philipp Kenel, William Kitch, Tetiana Kravchenko, Idoia Larretxi Lamelas, Edurne Simón Magro, Olaia Martinez Gonzalez, Martina Martinovic, Virginia Navarro Santamaria, Maria, Nemilentseva, Rana Parweeen, Andrea Pelzeter, Daria Podmetina, Manuel Quirós, Ellen Saltevo, Marina Schmitz, Elena Senatorova, Kai Shaman, Aušrinė Šilenskytė, Julia Solovjova, Unai Tamayo Orbegozo, Marko, Torkkeli, Itziar Txurruka Ortega, Gustavo Vargas-Silva, Anna Young-Ferris and Chuan Yu.